First Robotic Hepatectomy With Middle Hepatic Vein Reconstruction Using ePTFE Graft for Hepatic Adenoma: A Case Report - Wang, Jilong; Jin, Zongrui; Xu, Banghao; Chen, Weitao; Zhang, Jianyong; Zhu, Hai; Lu, Tingting; Zhang, Ling; Guo, Ya; Wen, Zhang (Frontiers in Surgery, 2022)
Surgical resection remains the best choice for the treatment of liver tumors. Hepatectomy combined with artificial vascular reconstruction has been proven as an alternative to treating tumors involving the main hepatic veins. As the cutting-edge surgical technique, robotic liver surgery is a novel procedure expanding the field of minimally invasive approaches, especially in complex reconstruction. This study reports, for the first time, on a robotic hepatectomy with middle hepatic vein (MHV) reconstruction using an expanded polytetrafluoroethylene (ePTFE) graft for a patient with hepatic adenoma. The tumor, which was located in segment 8, was adjacent to the MHV. Robot-assisted resection of segment 4 and partial segment 8, and MHV reconstruction using a ePTFE graft were performed. During the post-operative examination and follow-up, the blood flow of the ePTFE graft was patent, and liver function recovered well. Thus, robotic hepatectomy with MHV reconstruction is a safe, minimally invasive, and precise surgery that may provide a novel approach for patients with liver tumors that are invading or adjacent to the main hepatic veins.